2020
DOI: 10.1111/jfd.13304
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon sequencing reveals significantly increased Vibrio abundance and associated gene functions in vibriosis‐infected black tiger shrimp (Penaeus monodon)

Abstract: Vibriosis caused by luminous Vibrio species is one of the biggest challenges to shrimp industry in Bangladesh. This study aimed to characterize whole microbial communities from Vibrio‐infected black tiger shrimp (Penaeus monodon) using 16S rRNA‐based amplicon sequencing. A total of 36 disease‐free and infected shrimp were collected from six different hatcheries in Bagerhat, Bangladesh. A final pool of 12 samples (n = 6) was created by homogenization of the hepatopancreas samples from three shrimps collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…APM: Vp AHPND ‐infected; CTL: uninfected control; FH: Foysal et al. ( 2021 ) healthy; FI: Foysal et al. ( 2021 ) infected; HH: Hossain et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…APM: Vp AHPND ‐infected; CTL: uninfected control; FH: Foysal et al. ( 2021 ) healthy; FI: Foysal et al. ( 2021 ) infected; HH: Hossain et al.…”
Section: Resultsmentioning
confidence: 99%
“…( 2021 ) healthy; FI: Foysal et al. ( 2021 ) infected; HH: Hossain et al. ( 2021 ) healthy; HI: Hossain et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides Flavobacterium, Aeromonas bacteria were also found in shrimp A2. The existence of the Aeromonas bacteria group in the study of Foysal et al [36] showed that the genus Aeromonas was the most dominant bacterium, especially in the hepatopancreas of shrimp. Bravo and Figueras [32] explained that Aeromonas can be isolated from the aquatic environment and has been considered a group of pathogenic bacteria in humans and animals.…”
Section: Shrimp A2 Shrimp B2mentioning
confidence: 99%